Report of national consultations to launch fisherfolk organizations in: Dominica, Grenada, Guyana, St. Kitts and Nevis, St. Lucia, St. Vincent and the Grenadines (CRFM Secretariat [Belize City]BZ, 2007)
Reports on efforts to form National Fisherfolk Organizations, the concept of the Caribbean Network of National Fisherfolk Organizations (CARNUFO) and the likely benefits of using an organized network to help fisherfolk realize increased earnings, enhance social status and conserve the fishery resources.
Keywords: FISHERMEN